Determination of the critical velocity of a straight wing with a high aspect ratio - Thanh, Le Thi (Zielona Góra: Uniwersytet Zielonogórski)
An aerodynamic problem on an air flow around a large aspect ratio rectangular wing is investigated in this study. According to the theory of Vlasov, the wing is considered to be a thin rod. External loads are assumed to be proportional to the airfoil angle of attack related to the dimensionless coefficient of the lift and the pitching moment coefficient. These coefficients depend on the airfoil parameters and the Mach number M and are determined by experimental measurements for subsonic and supersonic velocities.
Keywords: thin rod; divergence; linear aerodynamics; straight wing; high aspect ratio; critical velocity